Genetic diversity among common bean (Phaseolus vulgaris L.) Greek landraces and commercial cultivars: nutritional components, RAPD and morphological markers - Mavromatis, A. G.; Arvanitoyannis, I. S.; Korkovelos, A. E.; Giakountis, A.; Chatzitheodorou, V. A.; Goulas, C. K. (Spanish Journal of Agricultural Research, 2010)
The genetic diversity among the main local landraces and commercial cultivars of P. vulgaris L. cultivated in Greece, was estimated by studying the morphological, agronomical and physicochemical traits along with molecular data analysis using random amplified polymorphic DNA (RAPD markers). Cluster analysis was conducted on similarity estimates using the UPGMA algorithm. Application of cluster analysis resulted in a dendrogram representing the genetic relationship among landraces and main bean cultivars grown in Greece. A wide genetic variation was observed among collected local bean landraces in morphological characteristics such as seed color, seed size and growth habit. According to agronomic performance, significant differences were found in number and weight of pods per plant. Variation in protein and fat content among landraces and commercial cultivars was also detected. Moreover, in some landraces like Kastoria and Byzitsa M/M extremely high values for protein content (28.6% and 27.0% respectively) were recorded. Such values were greater than the average protein content previously recorded for other cultivars of this species. Genetic similarity estimated from molecular analysis with RAPDs, seemed not to be related with the seed morphological characteristics and agronomic performance. Only qualitative parameters like growth habit and occasionally geographical origin of landraces were positively correlated with the molecular classification. Local bean landraces were classified in three subgroups whereas the commercial cultivars formed another separate group underlining the narrow genetic base of cultivars.